BANA-Positive Plaque Samples Are Associated with Oral Hygiene Practices and Not CD4+ T Cell Counts in HIV-Positive Patients - Cathy Nisha John; Lawrence Xavier Graham Stephen; Charlene Wilma Joyce Africa (Hindawi Limited, 2012)
Background. The "red complex" microorganisms, namely, Porphyromonas gingivalis, Treponema denticola, and Tannerella forsythia are considered as potential pathogens causing HIV-associated periodontal diseases. Moreover, it has been recognized that an association exists between CD4+ T cell counts and periodontal disease progression. Objective. To establish whether CD4+ T cell counts or oral hygiene plays a greater role in producing BANA-positive results in HIV-associated periodontal disease. Materials and Methods. One hundred and twenty HIV-positive patients participated in the study, and their CD4+ T cell counts were obtained from their medical records. The six Ramfjord teeth were used for evaluating periodontal clinical indices and subgingival plaque sampling. BANA test was used for the detection and prevalence of the "red complex" bacteria in plaque samples. Results. A majority of 69.17% HIV-positive patients were BANA-positive. No significant associations were found between BANA and CD4+ T cell counts. A highly significant association was found between BANA with probing depth and clinical attachment level (P≤0.0001) and between BANA and the use of interdental aids (P=0.0168). Conclusion. HIV-associated periodontal diseases are strongly related to oral hygiene practices rather than the effect of CD4+ T cell counts, and the use of interdental aids was marked as a significant predictor of BANA-negative plaque samples.